2006
DOI: 10.2527/jas.2006-028
|View full text |Cite
|
Sign up to set email alerts
|

Flavor relationships among muscles from the beef chuck and round1

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 12 publications
2
10
2
Order By: Relevance
“…Iron and zinc were reported previously (Nour et al, 1983) to have signifi cant positive phenotypic correlations with beefy fl avor (r = 0.33 and 0.34), respectively, although weaker phenotypic correlations were previously reported on the present data set (r = 0.14 and 0.06, respectively; Garmyn et al, 2011). Meisinger et al (2006) examined the relationship of heme iron to off-fl avor in different muscles from the chuck and round and a signifi cant correlation (−0.51) was identifi ed only between heme iron and offfl avor intensity for just 1 (vastus lateralis) of 7 muscles used in their study. The possibility exists for heme iron, by producing radicals capable of inducing lipid oxidation (Kanner and Harel, 1985;Batifoulier et al, 2002), to act as a pro-oxidant and infl uence meat fl avor.…”
Section: Relationships With Sensory Traitscontrasting
confidence: 63%
“…Iron and zinc were reported previously (Nour et al, 1983) to have signifi cant positive phenotypic correlations with beefy fl avor (r = 0.33 and 0.34), respectively, although weaker phenotypic correlations were previously reported on the present data set (r = 0.14 and 0.06, respectively; Garmyn et al, 2011). Meisinger et al (2006) examined the relationship of heme iron to off-fl avor in different muscles from the chuck and round and a signifi cant correlation (−0.51) was identifi ed only between heme iron and offfl avor intensity for just 1 (vastus lateralis) of 7 muscles used in their study. The possibility exists for heme iron, by producing radicals capable of inducing lipid oxidation (Kanner and Harel, 1985;Batifoulier et al, 2002), to act as a pro-oxidant and infl uence meat fl avor.…”
Section: Relationships With Sensory Traitscontrasting
confidence: 63%
“…Miller (2001) suggested cuts with greater levels of myoglobin have been associated with the liver-like off-flavor, and Yancey et al (2006) noted the liver-like off-flavor increased in the M. gluteus medius as iron increased. Meisinger et al (2006) reported that 55% of the variation of the liver-like off-flavor in the M. rectus femoris was due to heme iron content and pH. In the current study, neither heme iron nor pH was a part of the regression equation, and the simple correlations were not significant (data not shown).…”
contrasting
confidence: 64%
“…Meisinger et al (2006) reported that 55% of the variation of the liver-like off-flavor in the musculus rectus femoris was due to heme-Fe content and pH. Belk et al (1993) noted that cuts with no fat trim or cooked to greater degrees of doneness had more of the liver-like off-flavor compared with cuts with trimmable fat or cooked to lower degrees of doneness.…”
Section: Discussionmentioning
confidence: 99%
“…Meisinger et al (2006) reported that approximately Values presented on a DM basis. LALF = low alfalfa; HALF = high alfalfa; LSTALK = low corn stalks; HSTALK = high corn stalks; LSIL = low corn silage; HSIL = high corn silage.…”
Section: Introductionmentioning
confidence: 99%